Avaliação da toxidade de efluente da indústria alimentícia com o uso de microcrustáceo Daphnia magna e semente de alface Lactuca sativa - Freiberger, Vanessa Luisa (2017)
The process of treatment of industrial effluents has been increasingly studied due to environmental problems related to the disposal of these effluents in an often incorrect way, damaging the aquatic systems. In addition to the determination of toxic compounds present in the effluents, it is necessary to evaluate other parameters in parallel, in order to properly characterize the effluent. The objective of the present study was to characterize crude and treated effluent samples from the food industry through physicochemical analysis, to evaluate acute and chronic toxicity using the freshwater microcrustacean Daphnia magna as test organism and to evaluate the effects on germination with the lettuce seed Lactuca sativa. With the physicochemical characterization of all collected effluent samples, it was possible to verify the efficiency of the treatment carried out by the food industry, and thus the parameters dissolved oxygen and conductivity were those that did not reach values established by the legislation after the treatment. The acute test with daphnia magna indicated a toxic potential for two treated effluent samples (T1 and T2), which was in the range 1.97% and 9.54% and for the other samples (T3, T4 and T5) had no acute toxicity effects. On the other hand, the chronic test with Daphnia magna presented significant differences in the sample (T1) in the parameter number of postures and in the sample (T4) presented significant difference in all parameters. In the toxicity test with the Lactuca sativa seed, significant effect was observed in the germination and growth of the seedlings, the higher the dilution of the effluent sample, the worse the growth.